HISTORY, GOALS, AND HUMAN RESOURCES MANAGEMENT IN INTEGRATED ISLAMIC SCHOOL - Kasiman Kasiman; Siti Zakiah; Nasrudin Harahap; Nurul Hidayati Murtafiah (IAI An Nur Lampung, 2022)
Towards the 21st century, there are quite interesting changes regarding the trend of education in Indonesia. The dominance of Islamic educational institutions consisting of islamic boarding schools, madrasas, and schools began to shift, this was due to the emergence of Integrated Islamic Schools throughout the country. This Islamic educational institution has spread throughout Indonesia, first established by activists of the ITB campus mosque and UI. Such a rapid distribution of schools shows that the Integrated Islamic School is a new trend of Islamic education in Indonesia, this school emphasizes the education of religious moral values and excellent modern education today, this school also provides a new pattern regarding the reislamization of the Indonesian Muslim middle class. So the author is interested in conducting research related to the Integrated Islamic Coding Institute. In this study, the author uses a qualitative descriptive approach, which the author uses library research, namely collecting books related to the object of research or research that is literature. The Integrated Islamic School has the aim offostering students to become intelligent, noble muttaqien people who have skills that provide benefits and benefits for mankind, to achieve these goals, to implement good human resource management which includes various activities and processes namely, qualifications, recruitment patterns, employee orientation, employee wages, employee rules, coaching and development, employee assessment, employee career and rank, and welfare.